2019
DOI: 10.1016/j.dib.2019.104625
|View full text |Cite
|
Sign up to set email alerts
|

Data on small cardamom transcriptome associated with capsule rot disease

Abstract: Small cardamom (Elettaria cardamomum (L.) Maton, also known as the ‘Queen of Spices’ is a rhizomatous herbaceous monocot from the family Zingiberaceae. In the present study, using HiSeq™ 2000 RNA sequencing technology, transcriptome sequencing was performed for both control and disease stressed small cardamom leaf tissues. RNA-seq generated 46,931,637 (101 base) and 31,682,496 (101 base) raw reads and totally 9.93GB and 6.63GB of sequence data for cardamom control and stressed samples respectively. The raw dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Transcriptomic studies on leaves, stems, flowers, flower buds, capsule rot disease ( Nadiya et al, 2017 ; Mathew et al, 2019 ), mosaic virus disease ( Khan et al, 2020 ) of small cardamom, and Chirke disease ( Mathew et al, 2020 ) of large cardamom are reported. In turmeric species ( C. longa ), inter-cultivar differential gene expression in rhizomes of Nattu, Erode, Mysore, and Suvarna, along with SNP discovery, has been described ( Annadurai et al, 2013 ; Sahoo et al, 2016 ).…”
Section: Transcriptomic Studies: Comprehensive and Quantitative Resou...mentioning
confidence: 99%
“…Transcriptomic studies on leaves, stems, flowers, flower buds, capsule rot disease ( Nadiya et al, 2017 ; Mathew et al, 2019 ), mosaic virus disease ( Khan et al, 2020 ) of small cardamom, and Chirke disease ( Mathew et al, 2020 ) of large cardamom are reported. In turmeric species ( C. longa ), inter-cultivar differential gene expression in rhizomes of Nattu, Erode, Mysore, and Suvarna, along with SNP discovery, has been described ( Annadurai et al, 2013 ; Sahoo et al, 2016 ).…”
Section: Transcriptomic Studies: Comprehensive and Quantitative Resou...mentioning
confidence: 99%